Student Satisfaction Level on Academic and Administrative Services in FMIPA Universitas Negeri Manado - Kamagi, D D W (Journal of Educational Method and Technology, 2019)
Student satisfaction as users of academic and administrative services has been evaluated to find out the extent of service delivery that has been carried out by the academic and administrative work units of the Faculty of Mathematics and Natural Sciences, Universitas Negeri Manado. The level of student satisfaction with academic and administrative services has been measured using a linkert scale, and analyzed using the distribution of scores, then presented and served in tables or diagrams. Measuring the level of satisfaction of students to academic and administrative services covering six aspects, includingÂ tangibles, responsiveness, reliability, empathy, assurance and information systems. The six aspects are outlined in a question sheet with each aspect consisting of several question / statement items with the same score scale. Question points for all aspects of the assessment consisted of 42 items. The number of respondents amounted to 265 respondents. The measurement data is completely re-converted to get the level of student satisfaction with five categories, namely dissatisfied, less satisfied, quite satisfied, satisfied and very satisfied. The measurement results show that the level of student satisfaction with all aspects of academic and administrative services is 5.66% very satisfied, 23.02% satisfied, 38.11% quite satisfied, 24.91% less satisfied and 8.30% dissatisfied. While the level of student satisfaction with academic and administrative services for each aspect of service shows that only tangibles aspects are the percentage of satisfaction below 50%Â Keywords: Satisfaction; Academic and Administrative Services; FMIPA Students